2020
DOI: 10.3390/nu12113404
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Fat Diet Induced Obesity and Fructooligosaccharide Supplementation on Cardiac Protein Expression

Abstract: The mechanism by which high fat-diet induced obesity affects cardiac protein expression is unclear, and the extent to which this is modulated by prebiotic treatment is not known. These outcomes were assessed in rats initially fed a high-fat diet, then the top 40% weight gain group were randomly allocated to control (CON), high-fat (HF) and HF supplemented with fructooligosaccharide (32 g; HF-FOS) treatments for 12 weeks (n = 10/group). At sacrifice, left ventricles were either frozen or preserved in formalin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…In obese rats fed with an HFD for more than 12 weeks, a decrease in FA synthesis associated proteins and an increase in proteins involved in betaoxidation were observed. 20 Thomassen et al demonstrated that female rats fed with an HFD for 3 months had three times the peroxisomal beta-oxidation activity compared to male rats tissues. 26 Similarly, in another study conducted with hearts of obese rats, an increase in beta-oxidation caused activation of peroxisomes with increases in peroxisome protein levels (Abcd3 and Hsd17b4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In obese rats fed with an HFD for more than 12 weeks, a decrease in FA synthesis associated proteins and an increase in proteins involved in betaoxidation were observed. 20 Thomassen et al demonstrated that female rats fed with an HFD for 3 months had three times the peroxisomal beta-oxidation activity compared to male rats tissues. 26 Similarly, in another study conducted with hearts of obese rats, an increase in beta-oxidation caused activation of peroxisomes with increases in peroxisome protein levels (Abcd3 and Hsd17b4).…”
Section: Discussionmentioning
confidence: 99%
“…Increased lipid intake can be toxic for many tissues. In obese rats fed with an HFD for more than 12 weeks, a decrease in FA synthesis associated proteins and an increase in proteins involved in beta‐oxidation were observed 20 . Thomassen et al demonstrated that female rats fed with an HFD for 3 months had three times the peroxisomal beta‐oxidation activity compared to male rats tissues 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rats fed a 32% FOS diet for 12 weeks showed significantly increased hypertrophy of cardiomyocytes through subcellular changes in cardiac metabolism and contractility, which could affect myocardial function and alter the risk of CVD [79]. In humans, intake of barley or oat β-glucan at 3-5 g/day for 3-5 weeks improves blood lipid profile and reduces CVD risk factors such as body mass index, waist circumference, blood pressure, LDL, and triglyceride levels [80][81][82].…”
Section: Cvdmentioning
confidence: 99%
“…Fructans are polymers of fructose linked by -2,1 bonds; inulin is characterized as having longer polymerized chains, whereas FOS possesses shorter polymerized chains [ 35 ]. Rats fed a HFD for 12 weeks showed increased cardiomyocyte hypertrophy compared to rats on a control diet; however, this hypertrophy was not reversed with supplementation of FOS alongside the HFD [ 113 ]. CVD is an accumulation of long-term lifestyle habits; it is possible that 12 weeks of FOS was not a long enough intervention to see significant changes in cardiomyocyte physiology.…”
Section: 3 Prebioticsmentioning
confidence: 99%